STUDIES ON FlSH EGGS AND LARVAE FROM INDIAN WATERS 3. DEVELOPMENT Of EGG AND EARLY LARVA OF CYPSETURUS SPILOPTERUS (CUVIER AND VALENCIENNES) - Vijayaraghavan, P (Indian Journal of Fisheries, 2011)
STUDIES ON FlSH EGGS AND LARVAE FROM INDIAN WATERS 3. DEVELOPMENT Of EGG AND EARLY LARVA OF CYPSETURUS SPILOPTERUS (CUVIER AND VALENCIENNES)